Osamu Tezuka's anime and manga character sketchbook - Tezuka, Osamu, 1928-1989; Caleb D Cook (Richmond Hill, Ontario : Udon Entertainment Corp, 2015)
The grandfather of manga and anime, Osamu Tezuka created hundreds of unforgettable characters during his 40+ year career as an illustrator and animator. This book offers a collection of the character designs from several of Tezuka's animation projects
Translated from the Japanese
Keywords: Tezuka, Osamu, -- 1928-1989 -- Comic books, strips, etc; Comic books, strips, etc -- Japan -- Technique; Cartoon characters -- Japan; Cartooning -- Technique